Super simple things to do with water : fun and easy science for kids - Doudna, Kelly, frey50 (Edina, MN : ABDO Pub., 2011)
Presents several fun science experiments one can do with water.
Super simple science -- Water -- Work like a scientist -- Materials -- Bottled up -- Super simple siphon -- Pack it in -- Expand your horizon -- Sealed up tight -- Straw pole.
"Super sandcastle"--P. [4] of cover.
Keywords: Water -- Experiments; Science -- Experiments; Water -- Experiments; Science -- Experiments; Water -- Experiments; Science -- Experiments; Science -- Experiments; Water -- Experiments; Juvenile works